Analysis of Business Costs of Western Honey Bee (Apis mellifera) in Teluk Rimba Village, Koto Gasib District, Siak Regency - Suhada, Nur; Sribudiani, Evi; Isma, Olla; Mohta, Gandhiko; Darlis, Viny Volcherina; Lestari, Ika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
In Teluk Rimba Village, Koto Gasib Subdistrict, Siak Regency, there are honey bee (Apis mellifera) businesses. These consist of five owners: Depra Group and Abdullah Madu Riau, established in 2020, and Young Daffa Madu, Madu Munthe Family, and Tunas Mekar, established in 2024. The beehives are located in the Industrial Plantation Forest (HTI) area of PT. Arara Abadi, Minas-Rasau Kuning District. This study focuses on cost analysis and business feasibility. No previous research has provided information on the current condition, business overview, cultivation practices, or feasibility of the honey bee ventures. This research analyzes the production costs, revenues, income, and feasibility of the Apis mellifera honey bee business in Teluk Rimba Village, Koto Gasib Subdistrict, Siak Regency. This research uses a mixed-method approach combining both qualitative and quantitative methods. The data analysis includes descriptive analysis, cost analysis, revenue, income, and Revenue Cost Ratio (R/C ratio) analysis. The results show that the total production cost of the Apis mellifera honey bee business from January to December 2024 was IDR 492,393,331. The total revenue for the same period was IDR 1,055,775,000. The net income generated was IDR 563,381,669. The R/C ratio analysis for the five honey bee businesses, Young Daffa Madu, Madu Munthe Family, Tunas Mekar, Depra Group, and Abdullah Madu Riau, shows that the total revenue divided by total production cost yielded a value of 2.14. This indicates that the honey bee business is profitable and feasible for development, as the R/C ratio value exceeds 1